Experimental Investigation of a Self-Sensing Hybrid GFRP-Concrete Bridge Superstructure with Embedded FBG Sensors - Yanlei Wang; Yunyu Li; Jianghua Ran; Mingmin Cao (International Journal of Distributed Sensor Networks)
A self-sensing hybrid GFRP-concrete bridge superstructure, which consists of two bridge decks and each bridge deck is comprised of four GFRP box sections combined with a thin layer of concrete in the compression zone, was developed by using eight embedded FBG sensors in the top and bottom flanges of the four GFRP box sections at midspan section of one bridge deck along longitudinal direction, respectively. The proposed self-sensing hybrid bridge superstructure was tested in 4-point loading to investigate its flexural behavior and verify the operation of the embedded FBG sensors. The longitudinal strains of the hybrid bridge superstructure were recorded using the embedded FBG sensors as well as the surface-bonded electric resistance strain gauges. The experimental results indicate that the embedded FBG sensors can faithfully record the longitudinal strains of the hybrid bridge superstructure in tension at bottom flanges and in compression at top flanges of the four GFRP box sections over the entire loading range, as compared with the surface-bonded strain gauges. So, the proposed self-sensing hybrid GFRP-concrete bridge superstructure can reveal its internal strains in serviceability limit state as well as in strength limit state, and it will have wide applications for long-term monitoring in civil engineering.